The order parameter in binary mixtures - Patsahan, O.V. (Condensed Matter Physics, 1999)
Phase transitions in a binary mixture are investigated by means of the collective variables method with a reference system. It is shown that the system is described with two sets of collective variables: η~k and ξ~k. The CV connected with the order parameter is η~k₌₀ in the case of the gas-liquid critical point as well as in the case of the mixing-demixing phase transition. The particular form of η0 for each of these phenomena can be determined by means of the relations between the microscopic parameters,temperature, density and concentration of the system under consideration. Фазові переходи у бінарній суміші досліджуються з допомогою методу колективних змінних з виділеною системою відліку. Показано, що система описується двома наборами колективних змінних: η~k і ξ~k . Колективною змінною,зв’язаною з параметром порядку є змінна η~k₌₀ як у випадку критичної точки газ-рідина, так і у випадку фазового переходу змішування-незмішування. Конкретна форма η0 для кожного з цих явищ визначається співвідношенням між температурою, густиною, концентрацією і мікроскопічними параметрами системи, яка розглядається.